AB0829-HPR Influence of ra patient personality for more aggressive therapies. (23rd January 2014) - Leon, L.; Redondo, M.; Abasolo, L.; Garcia-Vadillo, A.; Gonzalez-Alvaro, I.; Arrieti, L.; Macarron, P.; Perez-Nieto, M. A.; Jover, J. A.
Abstract : Background: Actually, patients with rheumatoid arthritis (RA) play a more active role in relation to his illness, and the choice of treatment. The patient's personality can be an important part in this process. Few studies associate medical characteristics of the patient with prognosis and treatment. However, for the evaluation of RA using self-administered questionnaires (eg HAQ) or the patient's own assessment (DAS28), which are being influenced by patient characteristics such as personality. Objectives: To evaluate the influence of personality factors in the type of treatment that patients receive. Methods: Multicenter study of a cohort of patients with RA, with a crossover design. We selected patients diagnosed RA of recent onset in two hospitals, with a maximum follow-up of 18 months. All patients who consented completed a form that included general sociodemographic variables, the Eysenck Personality Questionnaire (EPQ-A), Locus of Control Health-related questionnaire (MHLC), and Beliefs and Self-statements about Pain questionnaire (PRCS / PRSS). Also collected measures of disease activity (DAS28 and CRP in the first year after diagnosis). Aggressive treatment was considered to have received more than two DMARDs, or Biological, during follow up. A descriptive analysis of the variables associated with more aggressive treatment and a logistic regression analysis to determine personality variables associated with treatment, adjusting for sociodemographic and clinical characteristics were performed. Results: A total of 176 RA patients were included in the study. 80% of the sample was women. The mean age was 55.7 ± 13.2 years. The 48.8% of the sample received aggressive treatment. The 50.89% of patients had high scores on extraversion, and 28.7% scored high in neuroticism. We do not found significant differences in age and sex related to aggressive treatment. We performed a multivariate logistic regression analysis, finding that the personality trait of neuroticism is the only predictor of receiving more aggressive treatment (p = 0.01, OR = 0.34). Conclusions: Patients with high scores on neuroticism are more worried, anxious and / or depressed, affecting their assessment of the disease and may influence the increased demand for therapeutic resources. Disclosure of Interest: None Declared